Additive manufactured thermal metamaterial devices for manipulating heat flow: geometric configuration design and SLM-assisted fabrication. (4th June 2021) - Deng, Tianxiang; Li, Bo; Xuan, Fuzhen
Abstract: Thermal metamaterials, benefitting from ingenious design and construction of artificial structures, commonly exhibit amazing heat conduction characteristics beyond naturally occurring materials in conventional scenarios. Based on the transformation thermodynamics theory and the effective medium theory, two types of metamaterial structure devices aiming to manipulate heat flow were artificially designed and fabricated with the aid of selective laser melting additive manufacturing technology in this work. The well-designed thermal metamaterial structures respectively achieved the thermal self-focus and thermal torsion functions. The relation of the configuration geometric parameters and the heat flux changes of the thermal metamaterial devices was carefully dissected. Following the geometric optimization design, the heat transfer directions achieved to be precisely manipulated as the design wishes. The changes in both heat flux and temperature distribution on the thermal self-focus and thermal torsion devices were traced through the numerical simulation and experimental measurement methods. The thermal simulation results were highly consistent with the experimental findings of the design-intended manipulation effects on the heat flow. The research work verified the applicability of the thermal metamaterial structures fabricated with the assist of selective laser melting in the thermal engineering fields.